Key elements of the structure of the country's national wealth ("Journal "U". Economy. Management. Finance.", 2024)
The article examines the elements of the structure of the country's national wealth, which include: human capital, financial capital, social capital, institutional capital, cultural capital, technological capital. The structure of the elements of national wealth demonstrates the complex nature of economic development. The relationships between the elements of national wealth allow us to form more effective economic policy strategies. A formula for the interaction of elements of national wealth is proposed, which reflects simple and complex interactions of the elements of the structure.
Keywords: national wealth; elements of the structure of national wealth; human capital; physical capital; natural resources; financial capital; social capital; institutional capital; cultural capital; technological capital